The impact of transportation fee on the performance of capital-constrained supply chain under 3PL financing service. (April 2019) - Huang, Shuai; Fan, Zhi-Ping; Wang, Xiaohuan
Highlights: 3PL financing service to capital-constrained retailer is considered. The 3PL firm's variable transportation fee is considered. Operational strategies of supply chain are examined under 3PL financing service. Performances of well-funded and capital-constrained supply chains are compared. Useful managerial insights for supply chain partners are given. Abstract: Under 3PL financing service mode, we study the impact of 3PL's transportation fee on the capital-constrained supply chain made up of a supplier, a capital-constrained retailer and a 3PL firm. In this paper, we assume that the 3PL firm can offer lower transportation fee to the retailer, if the retailer finances itself through the 3PL firm. First, we study the optimal operational strategies of the well-funded supply chain and the capital-constrained supply chain under 3PL financing service, respectively. In addition, we compare the optimal strategies and profits of supply chain enterprises under two cases, and also examine the impact of 3PL's transportation fee on the performance of capital-constrained supply chain. Through theoretical analysis and numerical simulation, two important conclusions are drawn. First of all, when the 3PL firm offers variable transportation fee strategy, the retailer's ordering quantity under 3PL financing service is more than that of a well-funded retailer if the transportation fee meets certain conditions. Otherwise the ordering quantity of a well-funded retailer is higher. Second, the variable transportation fee strategy of the 3PL firm cannot only increase the retailer's profit and the 3PL's profit, but also increase the total profit of the supply chain.